Not so fast: taste stimulus coding time in the rat revisited - Weiss, Michael S.; Di Lorenzo, Patricia M. (Frontiers in Integrative Neuroscience, 2012)
Behavioral and electrophysiological studies suggest that rats can identify a taste stimulus with a single lick, in <200 ms. Here, we tested the hypothesis that the number of licks of a tastant, its concentration and prior learning experience will modulate identification. In Experiment 1A, we trained rats to avoid licking a weak quinine solution (0.1 mM) by pairing it with a LiCl injection in the home cage. Control groups either received no experience with quinine or received both quinine and a LiCl injection that were unpaired. Rats were later water deprived and tested in an experimental chamber. A computer-controlled drinking spout allowed delivery of 1, 2 or 3 consecutive licks of tastants, interspersed with 5 water rinse licks presented on a variable ratio schedule. Tastants were quinine (0.1 mM, Q; 10 mM, HQ), NaCl (100 mM, N), saccharin (4 mM, S) and citric acid (10 mM, CA), dissolved in distilled water. Each rat was tested with Q, N, S, CA and water with 1, 2 or 3 stimulus licks on separate days. Rats showed evidence of Q avoidance/identification by the fourth interlick interval (ILI), 580 ms, but only after aversion training and only in the 3-lick condition. To assess the effects of the motivation, we divided each session into halves. Only one trained rat identified Q after ILI-3, 435 ms, in the second half of the session when given 3 licks of each stimulus. In Experiment 1B, we tested the same rats with HQ and found that all rats, regardless of learning condition, could identify quinine by ILI-4, 580 ms. In Experiments 2 and 3, rats were given a choice of Q or HQ vs. S and Q or HQ vs. sucrose (100 mM) in a 1-lick paradigm. Results showed that decreasing the number of choices of tastants in a session did not speed avoidance/identification of Q. Present data suggest that the neural representation of a taste stimulus may require only a single lick, but stimulus identification time may be a function of experience and motivation.